The Legal Aspect of Online Buying Transactions and Its Implications on Consumers - Azis, Abd.; Pattenreng, H. A. Muh. Arfah; Hamid, Haris (Postgraduate Bosowa University Publishing, 2018)
Online transaction is a transaction which are by spreading, purchasing, selling, marketing of goods and services by using online sales such a whatshAPP, facebook, instagram,etc. With online transaction it makes rofitable for consumers to choose varios types of goods but violations of consumers night by happen by online transaction like this. For the reason, legal protection is needed for consumers in online buying and selling transactions. Based on rule of government the article 4 letter h law number 8 off 1999 concerning consumer protection as explained that consumersare entitled to compensation, compensation, or compensation if the goods of services received are not accordance with the first agreement based on rule of government the article 7 letter g UUPK while business people obliged to give compensation or compensation if the goods and services received are not accordance by the agreement. Other than in electronic online transaction regording protection of consumers regulated in the article on rule government letter 1 number 6 of law number 11 of 2008 about the information and electronic transaction UU ITE which regulaters the organization of an electronic system are the utilization of an electronic system by state adminsttrators, personality, busyness entity, or community and the based on rule of government the article is letter 1 UU ITE regulaters that each an electronic system operator must carry out reliably, safely, and responsibly of the electronic system operatin.